Biophysical and structural characterization of nucleic acids: I. Structure, ions and folding/unfolding kinetics of left-handed G-quadruplexes II. Interaction of ligands with G-quadruplexes III. Characterization of nucleic acids on surface towards development of biosensors - Das, Poulomi (Nanyang Technological University, 2021)
G-quadruplexes are non-canonical structures of nucleic acid which has gained huge interest in the last few decades due to its crucial role in various biological processes, and for its applications as robust synthetic polymer in the field of therapeutics and nanotechnology. G-quadruplex structures are highly polymorphic and are able to modulate their structural characteristics depending on the environmental conditions. Various studies were only focused on right-handed G-quadruplexes, until the emergence of first left-handed G-quadruplex structure in 2015. Left-handed G-quadruplexes was reported to exhibit unique structural features, but their behavioral characteristics are rather unexplored owing to its recent discovery. A part of this dissertation is focused on studying the fundamental properties of left-handed G-quadruplexes, including its structural polymorphism, ion-exchange dynamics and folding/unfolding kinetics. Owing to their biological importance and association with several diseases, interactions of G-quadruplexes with ligands and proteins are of huge importance and abundantly studied. In this dissertation, we study the interaction of ligands and peptides with right- and left- handed G-quadruplex structures. The interaction study with ligands gives insight on the formation of G-quadruplex complexes in vivo and cell signaling processes, while the study with peptides can be essential for development of investigational probes and aptamers. Furthermore, we established the selectivity of canonical ligands and peptides on right-handed G-quadruplexes by explicitly showing that it does not bind to left-handed G-quadruplexes. Apart from natural DNA structures, various other synthetic forms of nucleic acids with chemical modifications have emerged, and are being extensively researched on, due to its potential applications in therapeutics and technological advancements. Two of such forms are locked nucleic acid (LNA) and peptide nucleic acid (PNA), which are reported to have superior properties than DNA, making them excellent candidates for biosensing probes. This dissertation investigates the dynamics of LNA and PNA tethered on an electrode surface and modulated by electric potentials. The study provides fundamental insights of the electrical properties of these nucleic acid structures which can be potentially used in the development of biosensors.